Optimising prescribing in older adults with multimorbidity and polypharmacy in primary care (OPTICA): cluster randomised clinical trial - Jungo, Katharina Tabea; Ansorg, Anna-Katharina; Floriani, Carmen; Rozsnyai, Zsofia; Schwab, Nathalie; Meier, Rahel; Valeri, Fabio; Stalder, Odile; Limacher, Andreas; Schneider, Claudio; Bagattini, Michael; Trelle, Sven; et al. (BMJ (Online), 2023)
AbstractObjectiveTo study the effects of a primary care medication review intervention centred around an electronic clinical decision support system (eCDSS) on appropriateness of medication and the number of prescribing omissions in older adults with multimorbidity and polypharmacy compared with a discussion about medication in line with usual care.DesignCluster randomised clinical trial.SettingSwiss primary care, between December 2018 and February 2021.ParticipantsEligible patients were ≥65 years of age with three or more chronic conditions and five or more long term medications.InterventionThe intervention to optimise pharmacotherapy centred around an eCDSS was conducted by general practitioners, followed by shared decision making between general practitioners and patients, and was compared with a discussion about medication in line with usual care between patients and general practitioners.Main outcome measuresPrimary outcomes were improvement in the Medication Appropriateness Index (MAI) and the Assessment of Underutilisation (AOU) at 12 months. Secondary outcomes included number of medications, falls, fractures, and quality of life.ResultsIn 43 general practitioner clusters, 323 patients were recruited (median age 77 (interquartile range 73-83) years; 45% (n=146) women). Twenty one general practitioners with 160 patients were assigned to the intervention group and 22 general practitioners with 163 patients to the control group. On average, one recommendation to stop or start a medication was reported to be implemented per patient. At 12 months, the results of the intention-to-treat analysis of the improvement in appropriateness of medication (odds ratio 1.05, 95% confidence interval 0.59 to 1.87) and the number of prescribing omissions (0.90, 0.41 to 1.96) were inconclusive. The same was the case for the per protocol analysis. No clear evidence was found for a difference in safety outcomes at the 12 month follow-up, but fewer safety events were reported in the intervention group than in the control group at six and 12 months.ConclusionsIn this randomised trial of general practitioners and older adults, the results were inconclusive as to whether the medication review intervention centred around the use of an eCDSS led to an improvement in appropriateness of medication or a reduction in prescribing omissions at 12 months compared with a discussion about medication in line with usual care. Nevertheless, the intervention could be safely delivered without causing any harm to patients.Trial registrationNCT03724539Clinicaltrials.gov NCT03724539